2008
DOI: 10.1161/circulationaha.107.762765
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thrombolysis Followed by Broad Use of Percutaneous Coronary Intervention With Primary Percutaneous Coronary Intervention for ST-Segment–Elevation Acute Myocardial Infarction

Abstract: Background-Intravenous thrombolysis remains a widely used treatment for ST-elevation myocardial infarction; however, it carries a higher risk of reinfarction than primary PCI (PPCI). There are few data comparing PPCI with thrombolysis followed by routine angiography and PCI. The purpose of the present study was to assess contemporary outcomes in ST-elevation myocardial infarction patients, with specific emphasis on comparing a pharmacoinvasive strategy (thrombolysis followed by routine angiography) with PPCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
2
23

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(122 citation statements)
references
References 27 publications
5
92
2
23
Order By: Relevance
“…For example, models of STEMI systems of care include that in Vienna with its city-wide system of care [10], France with the famous SAMU-nationwide system [11], Minneapolis [12] and Mayo clinic [13] with their regional system of care. Although they have some differences in the protocol, all of the systems are using a pharmaco-invasive approach.…”
Section: Discussionmentioning
confidence: 99%
“…For example, models of STEMI systems of care include that in Vienna with its city-wide system of care [10], France with the famous SAMU-nationwide system [11], Minneapolis [12] and Mayo clinic [13] with their regional system of care. Although they have some differences in the protocol, all of the systems are using a pharmaco-invasive approach.…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, real-world data from the French Registry on Acute ST-elevation Myocardial Infarction (FAST-MI), the Global Registry of Acute Coronary Events (GRACE), and the Canadian Registry of Acute Coronary Events (CANRACE) suggested better outcomes with routine angiography and revascularization after fibrinolytic therapy. 15,16 The American College of Cardiology Foundation/American Heart Association STEMI Guidelines also recommend angiography within 3 to 24 hours for patients who have received fibrinolytic therapy as an initial revascularization strategy.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 A recent study from the Acute Coronary Treatment and Intervention Outcomes Network (ACTION) registry demonstrated that 97.1% of fibrinolytic-treated STEMI patients received coronary angiography after transfer. 17 In our study, 95.5% of patients underwent coronary angiography after being transferred.…”
Section: Discussionmentioning
confidence: 99%
“…ФИС рассматривалась в иссле-дованиях как в контексте определения наиболее подходящей тактики ведения пациентов с ОИМпST после ТТ, которую проводили ввиду невозможности выполнения первичного ЧКВ в рекомендуемые вре-менные рамки по причине различных организацион-ных и логистических проблем (TRANSFER-AMI, CARESS-in-AMI, NORDSTEMI), так и в качестве возможной альтернативы первичному ЧКВ, когда очевидны задержки в проведении инвазивного вме-шательства -например, при переводе из другого стационара (FAST-MI, WEST, GRACIA-2, STREAM). В указанных исследованиях продемонстрировано преимущество раннего рутинного выполнения ЧКВ после ТТ над консервативной "выжидательной" стратегией, а также представлены сопоставимые результаты первичного ЧКВ и максимально быстро начатым тромболизисом с последующим обязатель-ным инвазивным вмешательством [25][26][27][28][29].…”
Section: таблицаunclassified